Effect of rib fat thickness on the quality of aged meat from Nellore young bulls - Dallantonia, Erick Escobar [UNESP] (2015)
This trial aimed to evaluate the quality of aged beef from Nellore young bulls under two yield grade (YG). Fourteen animals with approximately 450 ± 30 kg body weight were evaluated for backfat thickness (BFT) at the beginning of the experimental period. Seven animals had BFT of 0-3 mm and seven animals, 3.1-6 mm. Two groups were formed at the end of the experiment: animals finished with 3-6 mm BFT (seven animals) and animals finished with 6.1 to 10 mm BFT (seven animals). Every 28 days, we evaluated by ultrasound the BFT between the 12nd 13rd ribs. There was no interaction between YG and aging for beef color, pH, cooking losses and shear force (p > 0.05). There was no effect of YG on sarcomere length (p = 0.11). However, there was interaction between YG and aging on water holding capacity (p < 0.01). The yield grades evaluated did not interfere with meat quality, but carcasses with 6.1 - 10 mm of backfat thickness showed highest water holding capacity. The aging of the longissimus muscle for up to 14 days improves beef tenderness.